Beneficial Inner-City Quay Walls? - Philine C.R. Goldbohm; A. Rogier M. Wolfert; Jarit G. de Gijt; Mark L.C. de Bruijne; M A van Heesch (JACEE (Journal of Advanced Civil and Environmental Engineering), 2018)
Inner-city quay walls in public urban areas: expense or added value? These civil structures approach, reach or exceed the end of their life span. This threatens the quality of the public urban area. Many municipalities are still willing to invest in the management of inner-city quay walls, despite the costs. Apparently, the quay walls generate more benefits than that are initially expected based on their original functions. Until now, municipalities have failed to determine the added value of inner-city quay walls. Theoretical and practical research suggests that adequate asset management is indispensable. Nevertheless, no research focuses on valuable management of inner-city quays, in terms of performance, costs, benefits and risks. How to decide on a management strategy that adds the most value to the public area? A new framework should identify and incorporate the value of inner-city quay walls in the management process.